AN ALGORITHM OF FUZZY INFERENCE SYSTEM FOR HUMAN RESOURCES SELECTION TOOLS - Slavyanov, Krasimir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This article offers an original Human Resources selection procedure based on Mamdani fuzzy inference system (FIS) dedicated to compute multiple results each from different type of analyzing criterions. The modeling and information analysis of the FIS are developed to draw a general conclusion from several results each produced by Human Resources selection basic criterion. Simulation experiments are carried out in MATLAB environment.